2014
DOI: 10.3892/ijo.2014.2775
|View full text |Cite
|
Sign up to set email alerts
|

miR-224 overexpression is a strong and independent prognosticator of short-term relapse and poor overall survival in colorectal adenocarcinoma

Abstract: Colorectal adenocarcinoma constitutes the most frequent form of colorectal cancer and a serious cause of cancer-related deaths. The expression of multiple miRNAs, including miR-224, is deregulated in colorectal adenocarcinoma. The aim of this study was the investigation of the prognostic value of miR-224 in colorectal adenocarcinoma. For this purpose, total RNA was isolated from 115 colorectal adenocarcinomas and 66 adjacent non-cancer mucosae. Total RNA (2 µg) was polyadenylated and reverse transcribed. A qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 66 publications
1
24
0
1
Order By: Relevance
“…In addition to this discovery step, we analyzed two independent patient cohorts to validate that miR-139-5p is a potential biomarker for CRC recurrence. Supporting these results, several studies have reported that miRNAs such as miR-21, miR-29a, miR-34a, and miR-224 are deregulated during relapse and in metastatic CRC and were able to predict patients with high risk of recurrence28293031. However, these studies had several limitations, including inadequate sample size, lack of systematic and comprehensive discovery approach and lack of a validation patient cohort.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to this discovery step, we analyzed two independent patient cohorts to validate that miR-139-5p is a potential biomarker for CRC recurrence. Supporting these results, several studies have reported that miRNAs such as miR-21, miR-29a, miR-34a, and miR-224 are deregulated during relapse and in metastatic CRC and were able to predict patients with high risk of recurrence28293031. However, these studies had several limitations, including inadequate sample size, lack of systematic and comprehensive discovery approach and lack of a validation patient cohort.…”
Section: Discussionmentioning
confidence: 83%
“…The role of miR-224 during CRC initiation and progression remains controversial [15, 16, 17, 18, 19, 20, 21]: MiR-224 is overexpressed in inflammatory bowel disease-associated CRC [21], it promotes CRC tumor growth in mice by repressing PHLPP1 and PHLPP2 [19], and ectopic miR-224 expression decreases the chemoradiosensitivity of CRC [22], all of which suggests an oncogenic function. Yet, reports that methotrexate-resistant colon cancer cells express lower miR-224 [23], and that miR-224 suppresses tumor growth and metastasis in vivo [20] suggest that an opposite role in CRC may be true.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that an miRNA can have a predominantly oncogenic role in one type of cancer and a tumor suppressive role in another; for instance, miR-224 was identified to be a tumor suppressor in prostate cancer (30), whereas in other types of malignancy, including gastric (11,31) and colorectal cancer (32), an oncogenic role for miR-224 was described. The ambiguous role of miR-224 was also observed within the SCC histological subtype of NSCLC in the present study.…”
Section: Discussionmentioning
confidence: 99%